Saturday, 16 JUNE 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.2410
|View full text |Cite
|
Sign up to set email alerts
|

SAT0040 Safety, tolerability, pharmacokinetics and pharmacodynamics of bcd-089, novel monoclonal anti-il-6 receptor antibody: results from the first-in-human single dose escalation study in healthy volunteers

Abstract: BackgroundBCD-089 is a fully human monoclonal antibody targeting membrane-bound and soluble forms of IL-6Rα, thereby blocking of IL-6 classic and trans- signalling. IL-6, a proinflammatory cytokine, plays a central role in the pathogenesis of many chronic inflammatory and autoimmune diseases. Thereby inhibition of IL-6 signalling is a promising approach in the treatment of immune-mediated pathology.ObjectivesTo assess safety, immunogenicity, pharmacokinetics and pharmacodynamics of a single administration of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
4

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
1
0
4
Order By: Relevance
“…Ранее в ходе клинического исследования I фазы была определена дозозависимая нелинейная фарма кокинетика (ФК) ЛВЛ, типичная для ингибиторов ИЛ-6Р [7]. В данном исследовании показатель сывороточной концентрации ЛВЛ перед следующим введением (C trough ) был дозозависимым и демонстрировал более высокие значения в группе ЛВЛ 1 р./нед., чем в ЛВЛ 1 р./2 нед., во всех исследуемых временных точках (рис.…”
Section: оценка фармакокинетики и фармакодинамикиunclassified
See 3 more Smart Citations
“…Ранее в ходе клинического исследования I фазы была определена дозозависимая нелинейная фарма кокинетика (ФК) ЛВЛ, типичная для ингибиторов ИЛ-6Р [7]. В данном исследовании показатель сывороточной концентрации ЛВЛ перед следующим введением (C trough ) был дозозависимым и демонстрировал более высокие значения в группе ЛВЛ 1 р./нед., чем в ЛВЛ 1 р./2 нед., во всех исследуемых временных точках (рис.…”
Section: оценка фармакокинетики и фармакодинамикиunclassified
“…3). 3-й степени 4 (11,4) 5 (14,3) 2 (5,7) 4-й степени 0 0 2 (5,7) Повышение уровня АЛТ (всего) 7 (20,0) 8 (22,9) 5 (14,3) 3-й степени 2 (5,7) 3 (8,6) 2 (5,7) Повышение уровня АСТ (всего) 3 (8,6) 3 (8,6) 3 (8,6) 3-й степени 0 1 (2,9) 1 (2,9) Гиперхолестеринемия (всего) 13 (37,1) 11 (31,4) 4 (11,4) 3-й степени 1 (2,9) 2 (5,7) 0 Гипертриглицеридемия (всего) 7 (20,0) 5 (14,3) 5 (14,3) 3-й степени 4 (11,4) 2 (5,7) 0…”
Section: рис 4 показатели фармакокинетики и фармакодинамики лвл: концентрации лвл (A) с-реактивного белка (срб) (б) растворимого рецепторunclassified
See 2 more Smart Citations
“…Levilimab (LVL) is an original monoclonal antibody that binds to the alpha subunit of the IL-6 receptor (IL-6R) and blocks the transmission of IL-6 signal into cells. In a phase I clinical study LVL was well tolerated, showed favorable safety profile and low immunogenicity in doses ranged from 0.006 mg/kg to 2.9 mg/kg in healthy volunteers [ 7 ]. A phase II placebo-controlled clinical study showed that LVL 162 mg administered subcutaneously (SC) either once weekly (QW) or once every 2 weeks (Q2W) plus methotrexate (MTX) was superior to MTX alone in patients with active rheumatoid arthritis (RA) and inadequate response to MTX (NCT03455842) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%